Peran Pembimbing dalam Pembinaan Paduan Suara Gereja: Kajian Berdasarkan Amsal 11:14 di HKBP Pagar Beringin - Yosua Altiel Siburian; Irfan Firma Tua Berutu; Rangga Abednego Simare-mare; Novita Aditya Manalu (Jurnal Filsafat dan Teologi Katolik, 2026)
This study examines the role of the director in the development of the church choir at Huria (HKBP) Pagar Beringin using a theological approach based on Proverbs 11:14. The focus of this study is to understand how the director functions not only as a vocal technique coach but also as a leader, educator, and spiritual mentor who plays a role in building unity and the quality of the choir’s ministry. The method used is qualitative-descriptive through field research combined with a biblical study of Proverbs 11:14. The results of the study indicate that the successof choir development is highly dependent on the presence of a director who is ableto provide guidance, motivation, and wise counsel. Challenges such as a lack of understanding of vocal techniques, limited rehearsal methods, and low vocal homogeneity can be overcome through the role of an effective and contextual mentor. Theologically, the mentor is understood as the embodiment of God’s wisdom God who brings order, unity, and success inministry. Consequently, choir training is not only oriented toward musical quality but also toward spiritual growth, character development, and the creation of a harmonious ministry community that glorifies God.